Replacement of fishmeal in the diet of African catfish (Clarias gariepinus): a systematic review and meta-analysis - Saba, Abdulwakil Olawale; Fakoya, Kafayat Adetoun; Elegbede, Isa Olalekan; Amoo, Zakariyyah Olayiwola; Moruf, Rasheed Olatunji; Ibrahim, Musa Adamu; Akere, Taiwo Hassan; Muhammad Dadile, Abdulrahman; Adewolu, Morenike Adunni; Ojewole, Akinloye Emmanuel; Amal, Mohammad Noor Azmai (Universiti Putra Malaysia Press, 2023)
Fishmeal is widely accepted as a protein source in fish feed formulation, making it a highly demanded ingredient, and this has probably contributed to its increased cost. Cheaper protein sources of plant and animal origin have been tested as potential replacements for fishmeal to reduce feed costs in fish production and guarantee a suitable nutrient supply for adequate growth. Therefore, this review assessed the effect of replacing fishmeal in the diet of African catfish, Clarias gariepinus based on empirical findings. Using a systematic literature review protocol, an extensive search of five databases resulted in the final inclusion of 32 articles for appraisal and meta-analysis. Fishmeal replacements were at levels ranging from 7–100, while fish survival rate and feed conversion ratio recorded non-significant effects of fishmeal replacement (p > 0.05). However, final weight, weight gain, specific growth rate, and protein efficiency ratio revealed a significant effect of fishmeal replacement (p < 0.05) in the diet of African catfish. Our overall analyses suggest that feed ingredients such as microalgae and insects/worms are potentially perfect replacements for fishmeal.